Letter - Jones, J.W.
011-0144-001 Trade Union Delegation to Spain Committee. 3 Hale End Rd, E.17. Phone: LARkswood 1576. 4th. February. 1937. Sir. W. Citrine. General Secretary. T.U.C Dear Sir and Brother The above Committee which consists of eight Trade Unionists (J.Scott, A.E.U. A.F. Papworth, T. and G.W.U. O. Beamish, A.W.C. and S.H.J. Clayden. N.U.D.A.W. R.A. Sell, E.T.U. J. Jacobs, N.A.F.T.A. M. Finn, A.U.B.T.W. A.Davis, N.A.T.S.O.P.A.) has recently returned from Spain where they had the opportunity of meeting and discussing with prominent Spanish Trade Union Leaders the whole Spanish struggle. The Committee are anxious to meet you to place before you suggestions as to how best the Trade Union Movement in this country can assist our Spanish Comrades. Knowing your time to be fully taken up,they feel it necessary to point out the seriousness of the sitution,and trust you will find the time to meet them. I am, Yours fraternally, J.W Jones Secretary. 292/946/11/144